Answer: this is the awnser
Step-by-step explanation:
Answer:
y=2.6
Step-by-step explanation:
y/4=1.3/2
cross product
4*1.3=y*2
5.2=2y
y=5.2/2
y=2.6
Answer:
-a^2 + -a + 12
Step-by-step explanation:
Expand the following:
(3 - a) (a + 4)
(3 - a) (a + 4) = (3) (a) + (3) (4) + (-a) (a) + (-a) (4):
-a a + 3 a - 4 a + 3 4
3×4 = 12:
-a a + 3 a - 4 a + 12
-a a = -a^2:
-a^2 + 3 a - 4 a + 12
Grouping like terms, -a^2 + 3 a + 4 (-1) a + 12 = -a^2 + (3 a - 4 a) + 12:
-a^2 + (3 a - 4 a) + 12
3 a - 4 a = -a:
Answer: -a^2 + -a + 12
Answer:
-5-2
Step-by-step explanation:
10*+8=8
-5-2
big one is a great place to be written and then we are going to be able hi I love the way your house for me either ir you are you excited hi I love thet are ready for the good of the good